Influencing factors identification in smart society for insider threat in law enforcement agency using a mixed method approach - Karthiggaibalan Kisenasamy,; Valliappan Raman; Balveer Singh Mahindar Singh; Sundresan A/L Perumal (Springer Nature, 2024)
Indexed by WOS/SCOPUS